KELOMPOK BELAJAR SEBAGAI MODAL SOSIAL BELAJAR SISWA DI SEKOLAH - Susilawati, Nora (Humanus, 2013)
Study groups can be used as social capital for students in school. Through study groups, they can build a culture of learning that emphasizes togetherness. Thus, students can form social networks, solidarity, creativity and cooperation. It certainly can not be separated from student to student tardiness, students with teachers and teachers with other teachers. Kata kunci : study groups, social capital, culture of learning